Association of brachial-cuff excess pressure with carotid intima–media thickness in Australian adults: a cross-sectional study. Issue 4 (April 2020) - Peng, Xiaoqing; Wake, Melissa; Schultz, Martin G.; Burgner, David P.; Otahal, Petr; Mynard, Jonathan P.; Ellul, Susan; Cheung, Michael; Liu, Richard S.; Juonala, Markus; Sharman, James E.
Abstract : Objective: Reservoir pressure parameters [e.g. reservoir pressure (RP) and excess pressure (XSP)] measured using tonometry predict cardiovascular events beyond conventional risk factors. However, the operator dependency of tonometry impedes widespread use. An operator-independent cuff-based device can reasonably estimate the intra-aortic RP and XSP from brachial volumetric waveforms, but whether these estimates are clinically relevant to preclinical phenotypes of cardiovascular risk has not been investigated. Methods: The RP and XSP were derived from brachial volumetric waveforms measured using cuff oscillometry (SphygmoCor XCEL) in 1691 mid-life adults from the CheckPoint study (a population-based cross-sectional study nested in the Longitudinal Study of Australian Children). Carotid intima–media thickness (carotid IMT, n = 1447) and carotid–femoral pulse wave velocity (PWV, n = 1632) were measured as preclinical phenotypes of cardiovascular risk. Confounders were conventional risk factors that were correlated with both exposures and outcomes or considered as physiologically important. Results: There was a modest association between XSP and carotid IMT ( β = 0.76 μm, 95% CI, 0.25–1.26 partial R 2 = 0.8%) after adjusting for age, sex, BMI, heart rate, smoking, diabetes, high-density lipoprotein cholesterol and mean arterial pressure. Neither RP nor XSP were associated with PWV in the similarly adjusted models ( β = −0.47 cm/s, 95% CI, −1.15 to 0.20, partial R 2 = 0.2% for RP, and β = 0.04 cm/s, 95% CI, −0.59 to 0.67, partial R 2 = 0.01% for XSP). Conclusion: Cuff-based XSP associates with carotid IMT independent of conventional risk factors, including traditional BP, but the association was weak, indicating that further investigation is warranted to understand the clinical significance of reservoir pressure parameters.